IMPLEMENTASI MOORA PADA SELEKSI DOSEN TERBAIK BERDASARKAN HASIL PENILAIAN DALAM PEMBELAJARAN KULIAH - Hasirun Hasirun; Kusrini Kusrini; Kusnawi Kusnawi (Universitas Alma Ata, 2023)
Lecturer performance assessment is one of the activities of monitoring and evaluating performance with the aim of supervising the learning process and ensuring that lecturers carry out their duties in accordance with policies and teaching materials that have been determined. Lecturer performance assessment is carried out by students at the end of each semester by assessing lecturers based on criteria related to lecture learning. The criteria assessed in college learning are learning aspects, technological proficiency, integrity, and inspiration. The results of the student assessment will be reported to the learning development and quality assurance institution, which can later be used to determine the best lecturer performance. In this research, we apply the MOORA method to help determine the best lecturer based on assessment results in lecture reasoning. In its implementation, the MOORA method performs calculations based on criteria and weight values that have been determined and produces a ranking that can be used to determine the best lecturer's performance. In this study, the highest ranking was on the VPB alternative with a final value of 0.138, while the lowest value was on the DAM alternative with a final value of 0.108.